Some of fundamental methodological trends in contemporary developmental psychology - Otto, Kh. (Psichologija, 1983)
The article analyzes and evaluates critically these fundamental methodological trends of different countries in developmental psychology: - Developmental psychology research, - Mental characteristics and performance research, - Age and causal-genetic feature research, - Continuous and cross-sectional research, - Stating-descriptive and experimental-shaping research The article concludes by research-strategic conclusions.